ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PERUSAHAAN FURNITURE ( Studi Pada Karyawan Perusahaan Furniture Di Kecamatan Gemolong ) - Chuzaimah, Chuzaimah (Universitas Muhammadiyah Surakarta, 2008)
This Research aim to test the influence of ability work, relationwork, and satisfaction to compensation by parsial and also simultan to performance ofemployees at company furniture in region Gemolong. Population in this research all employees at company furniture in region of Gemolong Kab. Sragen, sampellimited only employees as much 44 people. Pursuant to the reason of intake sampel use the technique of Convenience Sampling. Technique of data collectinguse the questioner of while technique analyse the data use the multiple linear analysis regresion, the t test , the F test , and coefficient determination. The result analyse by multiple linear regresion obtain equation regresi that showed if ability work, relation work and satisfaction to compensation have influence at employees performance. Influence test by parsial indicate that the ability work the, relation work, and satisfaction to compensation by parsial have an effect on the significan to employees performance. This matter is proved from result the t test whereabout assess the t count > t tables. Influence test by simultan (F test) indicate that the ability work, relation work, and satisfaction to compensation by simultan have an effect on the significan to employees performance. This matter is proved from result the F test whereabout F count > F tables. Most variable itsdominant influence to employees performance is satisfaction to compensation, because value of coefficient regresion (b3 = 0,451) compared to by coefficient of regresion of ability work (b1 = 0,246) and coefficient of regresion of relation work the (b2 = 0,284).The value R2 showed that employees performance can be explained by ability work, relationwork, and satisfaction to compensation